The Relationship Between Residence With Parenting Style In Preschool Children - ovi maftukhatus maslukhah (Jurnal Ilmiah Keperawatan Indonesia (JIKI), 2021)
Parenting patterns are the active role of parents development of their children, there are several factors that influence parenting, one of  is the living environment, the environment where a family lives will cause the way parents apply parenting. This study aims to find the relationship between residence and parenting patterns of preschool children. This research is a quantitative study with an analytical survey research design with cross-sectional method.  Population of this research is all parents who have preschool age children in one kindergarten or SDN Bandar Agung in MUBA district and Bina Vita kindergarten in Palembang city with a large sample taken by purposive sampling technique totaling 116 respondents. The results showed that the parenting pattern of preschool children in rural areas was mostly authoritarian as much as 43.5%, parenting patterns for preschool children in urban areas were mostly permissive as much as 51.6%, and there was a relationship between residence and parenting patterns. preschool children with value = 0.000. This research  expected as information and contribution of thoughts to do parentingKeywords: Residence; Parenting Style; Preschool